Polymorphism in Crystals (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this reprint, several original pieces of research and reviews are collected on the topic of “Polymorphism in Crystals,” including the crystal structure determinations, the phase transformation studies, the thermodynamic and dissolution properties studies, the regulation of polymorph by additives and templates, the intensifications of the crystallization process, etc. This reprint aims to present and disseminate recent advancements in the design and use of polymorphism in crystals with desired qualities using crystal engineering. This reprint aims to enhance our understanding of polymorphism in crystals and their remarkably potential applications in pharmaceuticals, fine chemicals, and photoelectric industries.